Doping type effect on electrical conductivity of poly(2,6-dimethyl-1,4-phenylene oxide) and electrical properties of doped and undoped poly(2,6-dimethyl-1,4-phenylene oxide)/Ardel®D-100 films - Serin, M; Sakar, D; Cankurtaran, O; Karaman, F (NATL INST OPTOELECTRONICS, 2006)
The electrical conductivity of the polymer was measured in Al/polymer/Al structure over the temperature range of 300 - 510K. The measurements were carried out under vacuum of 10(-5) Torr and dark. The activation energies of the samples were determined. It was found that dopants such as tetra-n-butylammonium tetrafluoroborate, tetraethylammonium bromide, and tetra-n-butylammonium bromide do not increase the conductivity of poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) films prepared by cast method from chloroform solution with thickness of 6.0 mu m and at a rate of 0.50 mol doped/mol PPO. Then, the electrical properties of undoped poly(2,6-dimethyl-1,4-phenylene oxide)/Ardel (R) D-100 (PPO/ARDEL) film has been studied. The glass transition temperatures of the samples were determined by conductivity measurements. It was performed on PPO/ARDEL samples doped by tetra-n-butylammonium tetrafluoroborate in chloroform solution at the rates such as 0.25 mol doped/mol (PPO/ARDEL), 0.50 mol doped/mol (PPO/ARDEL) and 0.75 mol doped/mol (PPO/ARDEL). The conductivities of PPO/ARDEL blends are increasing as much as four orders of magnitude by increasing doping concentration.
Keywords: poly (2,6-dimethyl-1,4-phenyleneoxide); electrical characterization; dark conductivity; doping type; doping ratio; Materials Science; Optics; Physics